The Karazhaevs (materials for the genealogy) - Islam-Bek T. Marzoev (Кавказология, 2024)
Issues related to the genealogy of surnames currently arouse active public interest. This historical and genealogical study focuses on the Karazhaev surname, a prominent surname within North Ossetia’s Digor society.This study comprehensively examines the origins of the Karazhaev surname, as the princely family’s appearance in Ossetia remains unclear. Meanwhile, of great interest are the social and family ties of the Karazhaev representatives with the aristocracy of neighboring Ossetian societies and other Caucasian peoples: Kabardians and Balkars.The object of the study is the Karazhaev surname - one of the seven surnames of the Digor Badelates - descendants of Badeli.The study was conducted with the involvement of data from travelers and researchers of the 18th-19th centuries. The article presents information from the identified archival documents of the 19th century and published sources concerning the origin of the Karazhaev family name, the historical destinies of the representatives of this family in the 19th – early 20th centuries, during the era of revolutionary transformations in Russia and the Caucasus. As a result, materials from unpublished archival documents have been introduced into scientific circulation, such as documents from the “Committee established under the Military Ossetian District for the analysis of land and personal rights of the natives of this district”, family lists from the early 19th century, etc. The conducted research allows us to conclude that the Karazhaevs had close ethnocultural ties with neighboring Caucasian peoples. An analysis of archival documents and published sources show the high class and social status of the Karazhaev family, as well as their contribution to the development of socio-political and cultural ties between the peoples of the Caucasus and Russia, which is a powerful positive potential for stabilizing good-neighborly relations.